Avtoimunske bolezni ščitnice - Gržin, Lora (Placebo, 2022)
The most common thyroid diseases, Hashimoto thyroiditis and Basedow’s disease, are autoimmune diseases. The patients can form antibodies against thyroglobulin, thyroid peroxidase and TSH receptors which clinically manifests as a goiter. Hashimoto thyroiditis results in primary hypothyroidism, however, Basedow’s disease results in primary hyperthyroidism. Hashimoto thyroiditis is treated with hormone therapy, on the other hand, Basedow’s disease is treated with antithyroid active pharmaceutical ingredients, radioactive iodide and operational procedures. In the upcoming years we are expecting more research being conducted about the ethiopathogenesis of autoimmune thyroid diseases which will result in new treatment options since the therapy has not been changed in a while. One of the main reasons for the search of new active pharmaceutical ingredients in this field is the teratogeny of the ones already in use which is crucial since the incidence of Basedow’s disease in women at the age when giving birth is possible is high.
Keywords: Basedowova bolezen; biomarkers; Crohn's disease; golša; Hashimotov tiroiditis; inflammation; inflammatory bowel disease; pathophysiology; Ščitnica; Zdravljenje